2007
DOI: 10.1063/1.2720744
|View full text |Cite
|
Sign up to set email alerts
|

Pressure control model for transport of liquid mercury in carbon nanotubes

Abstract: Carbon nanotubes have a significant application in nanotechnology as nanopipes conveying fluids. In this letter, a pressure control model for transport of liquid mercury through carbon nanotubes using classical molecular dynamics simulations in conjunction with an atomistic model is presented. Wetting of single-walled carbon nanotubes by mercury occurs above a threshold pressure of liquid mercury. The liquid mercury can be transported through carbon nanotubes with the continuous increase of its internal pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Each pressure data point can be obtained by calculating the direct stress within each fluid subvolume. 26 The region between the two dashed lines ranging from 10 to 40 nm is selected to calculate the pressure gradient by performing a linear regression analysis. It is observed that the pressure of fluid decreases almost linearly along the fluid flow ͑x͒ direction, implying that a constant pressure gradient can be easily obtained by the channel moving pressure-driven model.…”
Section: ͑4͒mentioning
confidence: 99%
“…Each pressure data point can be obtained by calculating the direct stress within each fluid subvolume. 26 The region between the two dashed lines ranging from 10 to 40 nm is selected to calculate the pressure gradient by performing a linear regression analysis. It is observed that the pressure of fluid decreases almost linearly along the fluid flow ͑x͒ direction, implying that a constant pressure gradient can be easily obtained by the channel moving pressure-driven model.…”
Section: ͑4͒mentioning
confidence: 99%
“…2. A similar ejector model is adopted by Zhang et al (2007). Periodic boundary conditions along the x and y directions are applied on the simulation box.…”
Section: Simulation Modelmentioning
confidence: 99%
“…Interaction of fluids with microscopic pores by filling (imbibition) of nanotubes with oil or mercury is of great technological interest [22,23,24]. For example, inorganic nanotubes were successfully integrated with a microfluidic system to create a first nanofluidic device capable of sensing a single DNA molecule [24].…”
Section: Computer Simulation Of Fluid Flow In Nanotubesmentioning
confidence: 99%
“…Molecular dynamics and Monte Carlo methods were applied for studying microfluids [14,17,[20][21][22][23][24][25]. Propagation of acoustic waves on metal cylinders and through the carbon nanotubes was discussed in [37][38][39][40][41][42].…”
Section: Computer Simulation Of Fluid Flow In Nanotubesmentioning
confidence: 99%